Hubungan Pola Asuh Orang Tua Terhadap Kemandirian Anak Kelompok A2 Di Tk Aisyiyah Titang Boyolali Tahun Ajaran 2016/2017 - Purbowati, Shinta; , Drs. Haryono Yuwono, S.E.M.Pd (2017)
This research aim to determine the correlation between democracy parenting and the child's independence in group A at TK Aisyiyah Titang Boyolali. The population in this research were 32 students, and all the population were the sample for the research. This research used the correlation description research, with the technique of saturated Non-Probability Sampling. Technique of data collection used questioner, documentation and interview. Data analysis technique used the product moment correlation with the rarithmetic > rtable. The significant was about 1% = (0,553> 0,449) and 5% = (0,553 > 0,349). It meant that correlation was positive and strong. Based on the results of these calculations, it can be concluded that there is a positive correlation between democracy parenting and child's independence in group A at TK Aisyiyah Titang in The Academic Year of 2016/2017. Keywords: parenting democracy, independence of children